Perils, power and promises: Latent profile analysis on the attitudes towards artificial intelligence (AI) among middle-aged and older adults in Hong Kong - Ngai-Yin Eric Shum; Hi-Po Bobo Lau (Computers in Human Behavior: Artificial Humans)
With the increasing influence of artificial intelligence (AI) on various aspects of society, understanding public attitudes towards AI becomes crucial. This study investigated attitudes towards AI among Hong Kong middle-aged and older adults. In June 2023, an online survey was conducted among a sample of 740 smartphone users aged 45 years or older (Max = 78) in Hong Kong. Using exploratory factor analysis, we found three factors from the General Attitude to Artificial Intelligence Scale (GAAIS) - Perils, Power, and Promises. Subsequently, with latent profile analysis we revealed three latent profiles: (i) Enthusiasts (18.4%; high on Promises and Power but low on Perils); (ii) Skeptics (12.3%; high on Perils but low on Promises and Power), and (iii) Indecisive (69.3%; moderate on all three factors). The Enthusiasts were more likely to be male, with higher socio-economic status, better self-rated health, and greater mobile device proficiency, optimism, innovativeness, but also less insecurity with technology, compared to the Indecisive, and then to the Skeptics. Our findings suggest that most middle-aged and older adults in Hong Kong hold an ambivalent view towards AI, appreciating its power and potentials while also cognizant of the perils it may entail. Our findings are timely considering the recent debates on ethical use of AI evoked by smart phone applications such as ChatGPT and will be valuable for practitioners and scholars for developing inclusive AI-facilitated services and applications.